The Impact of Cybercrime on the Activities of Indigenous Entrepreneurs in Awka, Anambra State, Nigeria - Stanley Ikenna Onwuchekwe; Victora Onyeoziri; Tochukwu Emmanuel Madu; George Nweke Igboanugo; Mmesoma Agbodike (International Journal of Business, Economics, and Social Development, 2026)
In recent time, cybercrime has emerged as a critical threat to economic stability in Nigeria, with disproportionate effects on local economies. This paper examines the impact of cybercrime on the activities of indigenous entrepreneurs in Awka, Anambra, Nigeria. A cross-sectional survey research design was adopted. Questionnaires were distributed to 87 respondents purposively selected from 22 indigenous enterprises and key community wealth creators in the study area. The presentation of data was done using frequency distribution tables, charts and relevant narratives. The study found out that cybercrime undermines business growth through financial losses, erosion of customer trust, and reduced investor confidence. These disruptions extend beyond individual enterprises, contributing to declining household incomes, weakened reinvestment capacity, and slower community wealth distribution. The study identifies weak law enforcement, low digital literacy, and poor cyber security infrastructure as key enablers of cybercrime. The study, therefore, recommends multi-interventions, including digital security training for indigenous entrepreneurs, stronger regulatory enforcement, and community-based awareness programs, among others.